A Graphic Method of Estimating the Specificity of Screening Programmes from Incomplete Follow-up Data - Brecht, J. G.; Robra, B.-P. (Methods of Information in Medicine, 1987)
The specificity of a screening test determines, on the one hand, the extent of inconvenience and risk involved for healthy participants of a screening programme. This is, therefore, a possible determinant of programme acceptance. On the other hand, follow-up costs generally represent a considerable proportion of the total screening programme cost and are determined by the specificity. The specificity is thus an essential determinant of the efficiency of such a programme.Under the rare disease assumption it is possible to assess the specificity of screening programmes from cross-sectional data. On the basis of this method, a simple graphic way of evaluating the specificity is also described and illustrated by data stratified by age and screening history from the German National Cancer Screening Programme.
Keywords: Screening; Specificity; Prostate Cancer; Breast Cancer